Comparative Effect of a Renin Inhibitor and a Thiazide Diuretic on Renal Tissue Oxygenation in Hypertensive Patients - Nima Vakilzadeh; Marie-Eve Muller; Valentina Forni; Bastien Milani; Lucie Hoffman; Maciej Piskunowicz; Marc Maillard; Carole Zweiacker; Menno Pruijm; Michel Burnier (Karger Publishers, 2015)
Background/Aims: The purpose of the present study was to compare the direct renin inhibitor aliskiren to the diuretic hydrochlorothiazide (HCTZ) in their ability to modulate renal tissue oxygenation in hypertensive patients. Methods: 24 patients were enrolled in this randomized prospective study and 20 completed the protocol. Patients were randomly assigned to receive either aliskiren 150-300 mg/d or HCTZ 12.5 - 25 mg/d for 8 weeks. Renal oxygenation was measured by BOLD-MRI at weeks 0 and 8. BOLD-MRI was also performed before and after an i.v. injection of 20 mg furosemide at week 0 and at week 8. BOLD-MRI data were analyzed by measuring the oxygenation in 12 computed layers of the kidney enabling to asses renal oxygenation according to the depth within the kidney and by the classical method of regions of interest (ROI). Results: The classical ROI analysis of the data showed no difference between the groups at week 8. The analysis of renal oxygenation according to the 12 layers method shows no significant difference between aliskiren and HCTZ at week 8 before administration of furosemide. However, within group analyses show that aliskiren slightly but not significantly increased oxygenation in the cortex and decreased medullary oxygenation whereas HCTZ induced a significant overall decrease in renal tissue oxygenation. With the same method of analysis we observed that the response to furosemide was unchanged in the HCTZ group at week 8 but was characterized by an increase in both cortical and medullary oxygenation in aliskiren-treated patients. Patients responding to aliskiren and HCTZ by a fall in systolic blood pressure of >10 mmHg improved their renal tissue oxygenation when compared to non-responders. Conclusion: With the classical method of evaluation using regions no difference were found between aliskiren and HCTZ on renal tissue oxygenation after 8 weeks. In contrast, with our new method that takes into account the entire kidney, within group analyses show that aliskiren slightly increases cortical and medullary renal tissue oxygenation in hypertensive patients whereas HCTZ decreases significantly renal oxygenation at trough.